Specifics of translating the realities of the Yakut national dress into Chinese - Ordakhova Tuiaara; Grigoreva Anna (SHS Web of Conferences, 2022)
At the moment, the difference in cultures, linguistic pictures of the world is practically not an obstacle to mutual understanding between peoples. The given problems are completely surmountable in translation. Words and expressions that have no analogues in any other language can exist in the linguistic pictures of the world of one nation. Such words are called realities, namely, words that reflect the peculiarities of culture, customs and rituals of various nationalities. The study of realities plays a crucial role in comprehending the culture of another nation. It is significant not to forget your culture, to know all its subtleties and differences in the age of globalization and the free study of the language and culture of various nationalities. Translation of national dress can cause difficulty for the translator and this study is being conducted with the aim of simplifying this type of translation.